EFFECT OF ORGANIC AND INORGANIC FERTILIZERS ON GROWTH AND YIELD OF SUMMER SQUASH (Cucurbita pepo L.) - SHAREEF, REZAN SAEED; RASHEED, SANAA M.S.; ZEEBAREE, PASHTIWAN J.M. (Journal of Duhok University, 2022)
This experiment was carried out in the experimental vegetable farms of the Horticulture Department, College of Agricultural engineering sciences, University of Duhok, Kurdistan region, Iraq, during the spring growing season of 2021. The aim of the study was to investigate the response of summer squash cultivar, namely (Alexanderia  F1) to four levels of organic  (0 , 2 g.L-1 Fulvic acid, 2 g.L-1 Seaweed extract and 4 g.L-1 Amino acid  ) and three level of inorganic fertilizers ( 0, 1 ml.L-1 Cal-Mag and 5 ml.L-1 Phosphate-K) on growth and yield of summer squash plant (Cucurbita pepo L.). Fertilizers were used three times at the 25 days of planting and repeated in 10 days interval. Results showed that Spraying Summer squash with organic fertilizers especially amino acid significantly increased characters like (chlorophyll content in leaves, No. of fruit f.plant-1, plant yield kg.plant-1 and total yield t.ha-1), Also inorganic fertilizers especially Cal-Mag had higher increased  in characters ( plant length, leave area, chlorophyll content in leaves, No. of fruit f.plant-1, plant yield kg.plant-1 and total yield t.ha-1), where as no significant differences occurred in (Fruit length (cm), Fruit Diameter (cm) and TSS) by using organic and inorganic fertilizers